phoD-harboring bacterial community composition dominates organic P mineralization under long-term P fertilization in acid purple soil - Lang, Ming; Li, Haoming; Lakshmanan, Prakash; Chen, Yuanxue; Chen, Xinping (Frontiers in Microbiology, 2022)
A better understanding of the regulatory role of microorganisms on soil phosphorous (P) mobilization is critical for developing sustainable fertilization practices and to reduce P resource scarcity. The phoD genes in regulate soil organic P (Po) mobilization. Based on the long-term P application experiments in acid purple soil of maize system in Southwest China (started in 2010), the experiment included five P levels: 0, 16, 33, 49 and 65.5 kg P hm-2 (P0, P16, P33, P49 and P65.5, respectively). The molecular speciation of organic P in soil was determined by 31P-nuclear magnetic resonance (NMR), high-throughput sequencing technology and Real-time qPCR were used to analyze the bacterial community and abundance of phoD-harboring bacterial genes, exploring the bacterial community and abundance characteristics of phoD gene and its relationship with the forms of Po and alkaline phosphatase (ALP) activity in soil. The results showed that the orthophosphate monoesters (OM) were the main Po speciation and varied by P fertilization in acid purple soil. ALP activity decreased as P fertilization increased. Co-occurrence network analysis was identified the overall network under five P fertilization. The keystone taxon base on network showed that Collimonas, Roseateles, Mesorhizobium and Cellulomonas positively correlated with both OM and Po. The random forest showed Cellulomonas, Roseateles and Rhodoplanes were the key predictors for ALP activity. The keystone taxon were more important predictors than dominant taxon for ALP, OM and Po. The structural equation model (SEM) showed soil organic matter (SOM), available P (AP) and OM were the main factors influencing the ALP by reshaping phoD-harboring bacteria alpha-diversity, community composition and phoD abundance. The phoD-harboring bacterial community composition especially the keystone taxon rather than alpha-diversity and abundance dominated the ALP activity, which could promote P utilization over intensive agro-ecosystem. These findings improve the understanding of how long-term gradient fertilization influences the community composition and function of P solubilizing microorganisms in acid purple soil.